2006
DOI: 10.1161/01.res.0000214537.44195.a3
|View full text |Cite
|
Sign up to set email alerts
|

Electrotonic Modulation of Cardiac Impulse Conduction by Myofibroblasts

Abstract: Abstract-Structural remodeling of the myocardium associated with mechanical overload or cardiac infarction is accompanied by the appearance of myofibroblasts. These fibroblast-like cells express ␣-smooth muscle actin (␣SMA) and have been shown to express connexins in tissues other than heart. The present study examined whether myofibroblasts of cardiac origin establish heterocellular gap junctional coupling with cardiomyocytes and whether ensuing electrotonic interactions affect impulse propagation. For this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
387
4
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(430 citation statements)
references
References 35 publications
37
387
4
2
Order By: Relevance
“…For fibroblasts, previous studies using myocytefibroblast co-culture models have shown that the fibroblasts depolarized electrotonically coupled myocytes (Miragoli et al, 2006;MacCannell et al, 2007;Jacquemet and Henriquez, 2008;Maleckar et al, 2009). Our simulations also showed a depolarizing effect of coupled fibroblasts on the resting membrane potential of ventricular myocytes.…”
Section: Effects Of Fibroblast Coupling On Human Ventricular Myocyte supporting
confidence: 70%
See 2 more Smart Citations
“…For fibroblasts, previous studies using myocytefibroblast co-culture models have shown that the fibroblasts depolarized electrotonically coupled myocytes (Miragoli et al, 2006;MacCannell et al, 2007;Jacquemet and Henriquez, 2008;Maleckar et al, 2009). Our simulations also showed a depolarizing effect of coupled fibroblasts on the resting membrane potential of ventricular myocytes.…”
Section: Effects Of Fibroblast Coupling On Human Ventricular Myocyte supporting
confidence: 70%
“…In an experimental study, Miragoli et al (2006) found a biphasic effect on CV when endogeneous fibroblasts proliferated with myocytes. In a modeling study, Xie et al (2009a) showed that fibroblasts, whether coupled to myocytes or not, slowed conduction by creating zigzag conduction pathways.…”
Section: Effects Of Fibroblast Proliferation On CVmentioning
confidence: 98%
See 1 more Smart Citation
“…Our analysis also did not include any possible effects of myocyte-fibroblast connections as described in a recent paper by Miragoli et al 22 They demonstrated in cultured cells that a major electrotonic effect of such connections was to decrease the velocity of propagation along the cells. It seems unlikely, however, that such connections played a significant role in our experimental results because the average LP velocity of 9 uniform anisotropic pectinates without extensive fibrosis was less than the average LP velocity of the age preparations (Table 1).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Connexins are integral membrane proteins that form communicating junctions, or gap junctions. Connexin-43 was localized in hepatocytes, activated rat hepatic stellate cells, hematopoietic stroma cells, smooth muscle cells, fibroblasts (Ibuki et al 2002), myofibroblasts (Miragoli et al 2006), macrophages, thymocytes, and thymic epithelial cells. In our material (data not shown), double stains to connexin-43 combined with eosinophils or thy-1 or MAC-1 or B-220, showed that connexin-43 was expressed mainly by the middle or fibroblastic-like zone (myofibroblastic cells?)…”
Section: Discussionmentioning
confidence: 99%